Analysis of Insulin Resistance Levels in Patients with type 1 diabetes - Marjanović, Anja (Medicinski podmladak, 2024)
Introduction: Numerous studies to date have identified the presence of insulin resistance (IR) in type 1 diabetes (T1D), for which the estimated glucose disposal rate (eGDR) is determined.Aim: Analysis of IR levels in patients with T1D and comparison according to the presence of chronic complications of diabetes.Material and methods: The research was done in the form of a retrospective analysis of the database of medical records of 180 patients of both sexes with T1D, disease duration greater than one year in the period 2016-2021, who were divided into two groups based on eGDR levels - IRG (N = 86 , eGDR
Keywords: T1D, IR, cardiovascular risk, eGDR